2020
DOI: 10.1111/1541-4329.12179
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions of Plickers and crossword puzzles in undergraduate studies

Abstract: In higher education, there are calls to incorporate active learning experiences that place the student at the center of learning, rather than encouraging students to be passive listeners. For students to have a deeper and more meaningful learning experience, educators can use an active learning approach. This approach attempts to engage students at higher levels of thinking so that they are more interested in, better engaged with, and understand the course material better. The aim of this study was to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 32 publications
3
25
0
4
Order By: Relevance
“…Results also indicate that 21 and 25% of the students use mobile devices for their learning for the 2018 and 2019 cohorts, respectively. These results indicate that majority of the tech-savvy students can access teaching and learning content using their digital gadgets for learning (Mshayisa, 2020;Olivier, 2016). In higher education, digital technologies are seen as transformative tools for teaching and learning.…”
Section: Student Demographics and Online Accessmentioning
confidence: 89%
“…Results also indicate that 21 and 25% of the students use mobile devices for their learning for the 2018 and 2019 cohorts, respectively. These results indicate that majority of the tech-savvy students can access teaching and learning content using their digital gadgets for learning (Mshayisa, 2020;Olivier, 2016). In higher education, digital technologies are seen as transformative tools for teaching and learning.…”
Section: Student Demographics and Online Accessmentioning
confidence: 89%
“…We attributed this difference to the shorter puzzle administered to the BPharm group (10 clues) compared to the PharmD group (20 clues). Nonetheless, different studies reported described variable clues numbers ranging from 12 to more than 50 and completion time from 5 to 60 min, and all showed favorable agreement that the allocated time was adequate regardless of the size of the puzzle or completion time [ 36 , 38 , 48 , 51 – 53 , 57 – 60 ]. Notably, in the current study male students were less satisfied with the time provided for solving the puzzles than female students.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil kajian Mshayisa (2020) telah menunjukkan penggunaan Plickers dapat meningkatkan penglibatan pelajar dalam kelas. Selain itu, Plickers juga boleh ditawarkan sebagai instrumen pentaksiran formatif kos rendah.…”
Section: Sorotan Literaturunclassified
“…(Noraini, 2008). Plickers juga memberi kesan positif kepada hasil pembelajaran pelajar (Mshayisa, 2020). Terdapat 80% pelajar (24 orang) mempunyai peningkatan markah dalam ujian pos.…”
Section: Perbincangan Dapatan Kajianunclassified